TECHNOLOGY INTEGRATED PEDAGOGY AND LEARNING - Dildora Xusanovna, Kasimova; Sevinch Abror Qizi, Ikromova (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study investigates the integration of digital technologies in pedagogy and learning, with a focus on English language instruction and general academic contexts in non-English-speaking regions, particularly Uzbekistan. Method: Employing a qualitative descriptive approach, data were collected through interviews and observations involving both students and teachers to examine perceptions and experiences related to digital tools such as mobile applications, AI-assisted platforms, and digital libraries. Results: The analysis reveals that digital integration fosters learner autonomy, enhances access to information, and supports personalized learning. Students report improved efficiency and language development, while teachers recognize both the supportive potential and challenges of AI in instructional settings. However, issues such as over-reliance on technology, risks of academic dishonesty, and reduced interpersonal interactions are also identified. Novelty: Distinct from prior studies, this research offers a dual-perspective analysis—juxtaposing institutional pedagogical strategies with student lived experiences—and identifies specific digital applications that facilitate language acquisition and academic time management. The study emphasizes the importance of structured digital integration, informed digital literacy, and a balanced approach to innovation and academic integrity in higher education.